Bioleaching of Gold from Printed Circuit Boards: Potential Sustainability of Thiosulphate - Zahra Ilkhani; Farid Aiouache (Recycling)
The rapid consumption and disposal of electronic waste due to technological innovations and changes in living commodities are causing the development of a significant environmental challenge. Among the components of these wastes, spent printed circuit boards are particularly considered to be among the most valuable owing to their content of precious metals, such as gold first and potentially platinum, which may be available in a lower proportion. Effective methods as part of gold recovery strategies by industries and policymakers are developed and envisioned from economic and environmental perspectives. Currently, cyanidation dominates global gold production from e-waste due to its selectivity for gold. The high toxicity of cyanide, however, poses serious environmental issues, leading thiosulphate leaching to emerge as a non-toxic and promising alternative for gold extraction. Its industrial viability has been demonstrated by Barrick Gold Corporation at the Goldstrike site with the pretreatment of acidic or alkaline pressure oxidation. This review introduces bioleaching as a promising economic and environmentally friendly process for gold extraction. This review explores thiosulphate leaching of gold as an alternative to conventional cyanidation, with a particular focus on biothiosulphate production by adapted microorganisms. The factors that affect the pretreatment, chemical reaction mechanism, and design engineering are discussed. The consumption of thiosulphate was identified as one of the main challenges, restricting the reliability of the process. Various solutions for the reduction of its consumption and relevant process costs were discussed, with a particular examination from the engineering aspect of the process design and scalability to industrially relevant operating conditions by using bioreactors adapted to large pulp density loads of electrical waste.